Co-delivery of paclitaxel (PTX) and docosahexaenoic acid (DHA) by targeting lipid nanoemulsions for cancer therapy. (31st December 2022) - Li, Bo; Tan, Tingfei; Chu, Weiwei; Zhang, Ying; Ye, Yuanzi; Wang, Shanshan; Qin, Yan; Tang, Jihui; Cao, Xi
Abstract: Breast cancer is one of the most common types of cancer in female patients with high morbidity and mortality. Multi-drug chemotherapy has significant advantages in the treatment of malignant tumors, especially in reducing drug toxicity, increasing drug sensitivity and reducing drug resistance. The objective of this research is to fabricate lipid nanoemulsions (LNs) for the co-delivery of PTX and docosahexaenoic acid (DHA) with folic acid (FA) decorating (PTX/DHA-FA-LNs), and investigate the anti-tumor activity of the PTX/DHA-FA-LNs against breast cancer both in vitro and in vivo . PTX/DHA-FA-LNs showed a steady release of PTX and DHA from the drug delivery system (DDS) without any burst effect. Furthermore, the PTX/DHA-FA-LNs exhibited a dose-dependent cytotoxicity and a higher rate of apoptosis as compared with the other groups in MCF-7 cells. The cellular uptake study revealed that this LNs were more readily uptaken by MCF-7 cells and M2 macrophages in vitro . Additionally, the targeted effect of PTX/DHA-FA-LNs was aided by FA receptor-mediated endocytosis, and its cytotoxicity was proportional to the cellular uptake efficiency. The anti-tumor efficiency results showed that PTX/DHA-FA-LNs significant inhibited tumor volume growth, prolonged survival time, and reduced toxicity when compared with the other groups. These results indicated that DHA increases the sensitivity of tumor cells and tumor-associated macrophages (ATM2) to PTX, and synergistic effects of folate modification in breast cancer treatment, thus PTX/DHA-FA-LNs may be a promising nanocarrier for breast cancer treatment.